Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the expanded form of [tex]\((7x + 5)^3\)[/tex], we need to employ the binomial theorem.
The binomial theorem states that [tex]\((a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k\)[/tex], where [tex]\(\binom{n}{k}\)[/tex] is the binomial coefficient. In this particular case, [tex]\(a = 7x\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(n = 3\)[/tex].
Using the binomial theorem, we can expand [tex]\((7x + 5)^3\)[/tex] as follows:
[tex]\[ (7x + 5)^3 = \sum_{k=0}^{3} \binom{3}{k} (7x)^{3-k} 5^k \][/tex]
Let's break this down term by term:
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} (7x)^3 5^0 = 1 \cdot (7x)^3 \cdot 1 = (7x)^3 = 343x^3 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} (7x)^2 5^1 = 3 \cdot (7x)^2 \cdot 5 = 3 \cdot 49x^2 \cdot 5 = 735x^2 \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} (7x)^1 5^2 = 3 \cdot 7x \cdot 25 = 3 \cdot 7x \cdot 25 = 525x \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} (7x)^0 5^3 = 1 \cdot 1 \cdot 125 = 125 \][/tex]
Now, combining all these terms together, we get:
[tex]\[ (7x + 5)^3 = 343x^3 + 735x^2 + 525x + 125 \][/tex]
Thus, the fully expanded form of [tex]\((7x + 5)^3\)[/tex] is:
[tex]\[ 343x^3 + 735x^2 + 525x + 125 \][/tex]
The binomial theorem states that [tex]\((a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k\)[/tex], where [tex]\(\binom{n}{k}\)[/tex] is the binomial coefficient. In this particular case, [tex]\(a = 7x\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(n = 3\)[/tex].
Using the binomial theorem, we can expand [tex]\((7x + 5)^3\)[/tex] as follows:
[tex]\[ (7x + 5)^3 = \sum_{k=0}^{3} \binom{3}{k} (7x)^{3-k} 5^k \][/tex]
Let's break this down term by term:
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} (7x)^3 5^0 = 1 \cdot (7x)^3 \cdot 1 = (7x)^3 = 343x^3 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} (7x)^2 5^1 = 3 \cdot (7x)^2 \cdot 5 = 3 \cdot 49x^2 \cdot 5 = 735x^2 \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} (7x)^1 5^2 = 3 \cdot 7x \cdot 25 = 3 \cdot 7x \cdot 25 = 525x \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} (7x)^0 5^3 = 1 \cdot 1 \cdot 125 = 125 \][/tex]
Now, combining all these terms together, we get:
[tex]\[ (7x + 5)^3 = 343x^3 + 735x^2 + 525x + 125 \][/tex]
Thus, the fully expanded form of [tex]\((7x + 5)^3\)[/tex] is:
[tex]\[ 343x^3 + 735x^2 + 525x + 125 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.